At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To find the equation of a line with a given slope that passes through a specific point, we use the point-slope form of the equation of a line. The point-slope form is given by:
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
where [tex]\( m \)[/tex] is the slope, and [tex]\( (x_1, y_1) \)[/tex] is a point on the line.
Given:
- The slope [tex]\( m = 3 \)[/tex]
- The point [tex]\((-3, -5)\)[/tex]
Substitute these values into the point-slope form equation:
[tex]\[ y - (-5) = 3(x - (-3)) \][/tex]
Simplify the equation by performing the arithmetic operations:
[tex]\[ y + 5 = 3(x + 3) \][/tex]
Distribute the 3 on the right-hand side:
[tex]\[ y + 5 = 3x + 9 \][/tex]
To get the equation into slope-intercept form [tex]\( y = mx + b \)[/tex], isolate [tex]\( y \)[/tex] by subtracting 5 from both sides:
[tex]\[ y = 3x + 9 - 5 \][/tex]
[tex]\[ y = 3x + 4 \][/tex]
So, the equation of the line is:
[tex]\[ y = 3x + 4 \][/tex]
Therefore, the correct answer is:
A. [tex]\( y = 3x + 4 \)[/tex]
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
where [tex]\( m \)[/tex] is the slope, and [tex]\( (x_1, y_1) \)[/tex] is a point on the line.
Given:
- The slope [tex]\( m = 3 \)[/tex]
- The point [tex]\((-3, -5)\)[/tex]
Substitute these values into the point-slope form equation:
[tex]\[ y - (-5) = 3(x - (-3)) \][/tex]
Simplify the equation by performing the arithmetic operations:
[tex]\[ y + 5 = 3(x + 3) \][/tex]
Distribute the 3 on the right-hand side:
[tex]\[ y + 5 = 3x + 9 \][/tex]
To get the equation into slope-intercept form [tex]\( y = mx + b \)[/tex], isolate [tex]\( y \)[/tex] by subtracting 5 from both sides:
[tex]\[ y = 3x + 9 - 5 \][/tex]
[tex]\[ y = 3x + 4 \][/tex]
So, the equation of the line is:
[tex]\[ y = 3x + 4 \][/tex]
Therefore, the correct answer is:
A. [tex]\( y = 3x + 4 \)[/tex]
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.